Уточненные шкалы пространств и эллиптические краевые задачи. II - Михайлец, В.А.; Мурач, А.А. (Український математичний журнал, 2006)
Вивчаються уточнені шкали функціональних гільбертових просторів на Rn та гладких многовидах з краєм. Елементами цієї шкали є ізотропні простори Хермандера-Волевіча-Панеяха. Розроблено теорію еліптичних крайових задач у цих просторах. We study improved scales of functional Hilbert spaces over Rn and smooth manifolds with boundary. The isotropic Hörmander-Volevich-Paneyakh spaces are elements of these scales. The theory of elliptic boundary-value problems in these spaces is developed.